Study of the effects of unsupervised over‐the counter whitening products on dental enamel using μ‐Raman and μ‐EDXRF spectroscopies. (8th December 2015) - Castro, J.; Godinho, J.; Mata, A.; Silveira, J. M.; Pessanha, S.
Abstract : The purpose of this in vitro study was to assess whether the mineralization degree and elemental content in tooth enamel are altered when bleaching the teeth with two different over‐the‐counter bleaching gels, exceeding the recommendations of the manufacturer. In order to perform this evaluation, 12 healthy teeth were used, six samples were treated with Teeth Whitening Home Kit, and the other six samples were treated with WHITE! (Bingo‐UK) bought in online shopping sites, for the period of 39 days. The pH of each product and the elemental content of each sample, before and after, were obtained by energy dispersive X‐ray spectrometry and phosphate (PO4 3‐ ) profile was evaluated with Raman spectroscopy. Data was analyzed accordingly to a pre‐established plan with a mixed‐model ANOVA for repeated measures, significance was set at 5%. Both products were markedly acidic and below enamel critical level of 5.5. Moreover, seven days after treatment, demineralization was significant, wherein at the end of the study the degree of demineralization seems to be permanent. Copyright © 2015 John Wiley & Sons, Ltd. Abstract : This in vitro study assesses whether the mineralization degree and elemental content in tooth enamel are altered when using over‐the‐counter bleaching gels, exceeding the manufacturer's recommendations. The elemental content of each sample was obtained by energy dispersive X‐ray spectrometry and phosphate (PO4 3‐ ) profile was evaluated with Raman spectroscopy. Seven days after treatment, demineralization was significant and was not fully recovered during the study.